2016
DOI: 10.3390/ijms17050729
|View full text |Cite
|
Sign up to set email alerts
|

The Use of 1α,25-Dihydroxyvitamin D3 as an Anticancer Agent

Abstract: The notion that vitamin D can influence the incidence of cancer arose from epidemiological studies. The major source of vitamin D in the organism is skin production upon exposure to ultra violet-B. The very first observation of an inverse correlation between exposure of individuals to the sun and the likelihood of cancer was reported as early as 1941. In 1980, Garland and Garland hypothesised, from findings from epidemiological studies of patients in the US with colon cancer, that vitamin D produced in respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 114 publications
(119 reference statements)
1
24
0
Order By: Relevance
“…The effect of 1,25(OH)2D3 on cell proliferation can also be mediated in an indirect way, via interference to the function of estrogen receptors (ER) (Marcinkowska, Wallace, & Brown, 2016). Intracellular calcium also plays a critical role in many fundamental processes such as proliferation, apoptosis, and secretion and any disruptions in calcium homeostasis play a critical role in tumor progression in most cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of 1,25(OH)2D3 on cell proliferation can also be mediated in an indirect way, via interference to the function of estrogen receptors (ER) (Marcinkowska, Wallace, & Brown, 2016). Intracellular calcium also plays a critical role in many fundamental processes such as proliferation, apoptosis, and secretion and any disruptions in calcium homeostasis play a critical role in tumor progression in most cancer.…”
Section: Discussionmentioning
confidence: 99%
“…diated in an indirect way, via interference to the function of estrogen receptors (ER)(Marcinkowska, Wallace, & Brown, 2016).1,25(OH)2D3 and its analogs reduce the expression of ERα, which F I G U R E 3 Clonogenic assay performed in 6-well plates in MCF7 cells. (a) Untreated clones after seeding 1,000 cells/well-(DMSO) with 60 and 56 clones, respectively; D treatment group had 30 and 26 clones per well, respectively; SFN group had 11 and 30 and D + SFN group had 33 and 22 clones, respectively.…”
mentioning
confidence: 99%
“…The multifunctional pro-hormone vitamin D (VD) and its metabolites activate transcriptional factor VR receptor (VDR)-mediated signaling [1]. The active vitamin D metabolite, 1α,25-dihydroxyvitamin D 3 (calcitriol) regulates cell proliferation and differentiation in cancerous and non-cancerous cells [2,3]. VDR agonists such as calcitriol and its analogs have been shown to exert the potent antiproliferative effects in breast cancer cells [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In the past, studies found that the asset of vitamin D was modified in patients with various forms of cancer, but it was not until recent that it was found that vitamin D actually has a modulating effect on cancer cells 25 : 1,25(OH)2 D stimulates the expression of cell cycle inhibitors p21 and p27 26 and the expression of the cell adhesion molecule E-cadherin, while inhibiting transcriptional activity of β-catenin. 27,28 These actions should block the proliferative potential of these cells.…”
Section: Mechanism Of Actionmentioning
confidence: 99%